Horray's Course Review Learning Model on Mastery of Arts and Culture Material and Skills for Students - Aidil Saputra; Rahmat Saputra; Pipi Mardalena (Seutia Hukamaa Cendekia, 2025)
The research aims to discover how the Course Review Horray learning model affects the mastery of arts and culture material and skills in class V students at MIN 18 West Aceh. To find out what obstacles teachers have in using the Course Review Horray learning model for class V students at MIN 18 West Aceh. This research method uses the Field Research type of research. Data collection uses interviews, observation and document study. Data analysis uses data reduction, data analysis, and conclusion. The results of the research show that the application of the Course Review Horay learning model to class V students at MIN 18 West Aceh can increase students' learning motivation, the application of the Course Review Horray learning model can make students appreciate differences more, take advantage of their strengths and fill each other's shortcomings, but the This learning must be more focused. For teachers who will apply the Course Review Horay learning model, it is best first to prepare the questions that will be drawn, and teachers must be good at dividing their time because the Course Review Horay learning model takes a long time. Apart from that, teachers must be good at controlling the class, and this is because the Course Review Horay learning model still has weaknesses, namely when controlling quite a lot of students.